Strategi Pengembangan Sumber Daya Manusia (SDM) Baitul Mal Wat Tamwil di Sumatera Utara - Rina Fitriani; Sri Sudiarti; Fauzi Arif Lubis (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the current state of the internal and external environment of BMT human resources in North Sumatra to determine the baitul mal wat tamwi human resource development strategy in North Sumatra. This type of research uses a qualitative approach using a SWOT analysis. This research was conducted directly at BMTs in North Sumatra, namely BMT Masyarakat Madani, BMT Raudhah, and BMT Al-Musabbihin. The research time started in June 2022, and it is finished. The researchers obtained it from the company and managers in the company, including managers and administrators in the two BMTs. The research object in question is the Human Resources (HR) development strategy for BMT Civil Society, BMT Raudhah BMT Al-Musabbihin, and its influence on the resilience of BMT and its impact on the welfare of MSMEs. The primary data source in this thesis is taken from answers to questionnaires distributed to respondents through direct interviews with the subject of the BMT management or those in charge of the BMT institution.Data obtained from other sources, researchers also include secondary data as a reinforcement of arguments, both from various literature such as previous research journals, both national and international, books, statistical data, and so on. After being seen from the internal environment, the study results stated that the BMT Human Resource Development Strategy in North Sumatra consisted of strengths, namely clear legal aspects of BMT and good relations between employees. At the same time, the weaknesses consist of human resources who tend not to be graduates of Islamic economics, family management, and human resource capabilities and competencies that still need them. Not active in the BMT forum/organization. When viewed from the external environment, it consists of opportunities, namely Linkage with Islamic Banks. At the same time, the threats are the lack of government support, minimal financial support, and the issue of the industrial revolution 5.0. A microfinance institution emerged. Furthermore, based on the results of the SWOT matrix analysis, after processing the IFE and EFE matrices, the resulting strategy quadrant is in quadrant 1, namely the progressive strategy. The approach used to develop BMT human resources in North Sumatra is the BMT SO Strategy will continue to make clear legality as a reinforcement for the establishment of BMT, continue to establish good relations between employees and take advantage of BMT links with Islamic Banks. As a strategy analysis from the author for BMT to utilize digitalization of BMT in promoting the presence of BMT or other social media.